Friction-thermal-vibration Coupling Analysis of Large-megawatt Wind Turbine Brake. (January 2019) - Zhang, S; Xin, P; Yin, J; Liu, Y; Sha, Z; Ma, F; Yang, D
Abstract: To establish a mutual contact relationship between the brake disc and the brake pad, simulation of the brake disc in the actual working conditions braking deceleration, according to the wind of the brake and brake piece of actual size and related parameters of brake disc material in ABAQUS to establish 3D transient friction-thermal-vibration coupling finite element model. The brake process is verified with the analysis of brake and brake disc contact, from the coupling results, this paper summarizes the temperature and stress distribution, the research on the temperature in time and space distribution. In this paper, the stress of brake stress is analyzed, and the distribution of stress is summarized, and the importance of the coupling study on the stress analysis of brake is analyzed.